Superficial‐Layer‐Enhanced Raman Scattering (SLERS) for Depth Detection of Noncontact Molecules. Issue 4 (28th November 2018) - Qiao, Xuezhi; Xue, Zhenjie; Liu, Lu; Liu, Keyan; Wang, Tie
Abstract: Although the strength of Raman signals can be increased by many orders of magnitude on noble metal nanoparticles, this enhancement is confined to an extremely short distance from the Raman‐active surface. The key to the development of Raman spectroscopy for applications in diagnosis and detection of cancer and inflammatory diseases, and in pharmacology, relies on the capability of detecting analytes that are noninteractive with Raman‐active surfaces. Here, a new Raman enhancement system is constructed, superficial‐layer‐enhanced Raman scattering (SLERS), by covering elongated tetrahexahedral gold nanoparticle arrays with a superficial perovskite (CH3 NH3 PbBr3 ) film. Plasmonic decay is depressed along the vertical direction away from the noble metal surface and the penetration depth is increased in the perovskite media. The vertical penetration of SLERS is verified by the spatial distribution of the analytes via Raman imaging in layer‐scanning mode. Abstract : Superficial‐layer ‐enhanced Raman scattering is constructed by covering elongated tetrahexahedral gold nanoparticle arrays with a superficial perovskite film to detect analytes that are noninteractive with Raman‐active surfaces. This technique has potential applications in diagnosis and detection of cancer and inflammatory diseases, and in pharmacology.